Does this fit? : a study of the perspectives of Home Detention Probation Officers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Social Policy, Massey University - Ward, Avril Eileen (Massey University, 2007)
The thesis is a qualitative study informed by Standpoint Theory (Smith, 1997) examining the perspectives of six Home Detention Probation Officers (HDPO's). In particular, the research explores the participants' perspective of two of the three major objectives of the Home Detention Order outlined in the Community Probation Service Operations Manual (CPSOM) Volume four. These are to: a) ensure that the criminogenic needs are met by the constructive use of programmes; and b) to ease the transition of inmates back into the community through a staged process of release by providing support and control structures. The research questions were focused on the 'fit' between the two objectives, the part the objectives and electronic monitoring play in guiding practice, and the combined impact of these on the everyday practice of HDPO's. The primary questions explored whether these objectives are working or achievable, what supports them and what barriers exist to their effective operations. The findings of this research show that, while the stated objectives are achievable, the fit between the manual and everyday practice for the participants could be challenging due to high caseloads, management regime requirements and areas within the manual and policy that were considered sparse, effectively leaving HDPO's without clear guidelines or procedures. Programmes were considered vital to home detention but issues around rescheduling, entry criteria to programmes and availability of programmes caused concern. Participants identified training areas such as working with families, combined with practice-based training would assist their practice delivery. They suggested that regular conference based trainings and meetings would inform policy and clarify practice issues, for instance in relation to after hours incidents. Electronic monitoring was considered to be a major component of home detention, however equipment reliability and communication problems with the monitoring company created difficulties with effective management of home detention.
Keywords: New Zealand; Probation officers; Attitudes; Home detention